Backyard poultry farming with improved germplasm: Sustainable food production and nutritional security in fragile ecosystem - Singh, Mahak; Mollier, R. T.; Paton, R. N.; Pongener, N.; Yadav, Rekha; Singh, Vinay; Katiyar, Rahul; Kumar, Rakesh; Sonia, Chongtham; Bhatt, Mukesh; Babu, S.; Rajkhowa, D. J.; et al. (Frontiers in Sustainable Food Systems, 2022)
Approximately 3 billion people were unable to afford a healthy diet in 2019 because of poverty and inequality. Most of these people live in Asia and Africa. Furthermore, 30% of the world population was affected by moderate to severe food insecurity in 2020, and most of this population lives in low- and middle-income countries. The world is at a critical juncture, and there is an urgent need for transformative food systems that ensure the empowerment of poor and vulnerable population groups, often smallholders with limited access to resources or those living in remote locations, as well as the empowerment of women, children, and youth (FAO, 2018). The backyard poultry production system (BPPS), as practiced by 80% of the world's rural population, can be that transformative change in low- and middle-income countries. Although the BPPS has low productivity, it still plays an important role in the food and nutritional security of rural people living in fragile ecosystems. Backyard poultry has been recognized as a tool for poverty alleviation and women empowerment besides ensuring food and nutritional security for rural poor. Poultry meat and eggs are the cheapest and best source of good quality protein, minerals, and vitamins. The introduction of improved backyard poultry germplasm has improved the productivity of this system in resource-poor settings and thereby improved the income and nutritional security of poor households. With these birds, the availability, access, utilization, and stability of food security have improved at household and national levels. Diseases, predation, non-availability of improved germplasm, lack of access to markets, and lack of skills are the major constraints to the adoption of improved backyard poultry. These constraints can be addressed by involving a network of community animal service providers. The improved backyard poultry germplasm will dominate the backyard poultry production system in the future and will be a tool for ensuring food and nutritional security on a sustainable basis, more particularly in low- and middle-income countries.